Regional Autonomy and Regional Government - Abdul Hakim; Fadil Almahdy Hasibuan; Watni Marpaung (AT-TAFAHUM: Journal of Law, 2023)
Regional autonomy is a crucial pillar of the Indonesian government system, aiming to grant local governments the authority to regulate and manage government affairs based on local potential and needs. The implementation of regional autonomy is expected to improve the effectiveness of governance, the quality of public services, and promote equitable development across regions. However, the implementation of regional autonomy still faces various challenges, particularly in institutional capacity, fiscal independence, and coordination between the central and regional governments. This study aims to examine the concept, legal basis, implementation, and challenges and efforts to strengthen regional autonomy within the Indonesian regional government system. The research method used is library research with a normative juridical approach, emphasizing the study of relevant laws and regulations and scientific literature. The research stages include the collection of primary and secondary legal materials, qualitative analysis through legal interpretation, and the systematic compilation of the study results. The results indicate that regional autonomy has provided space for local governments to exercise authority more independently, particularly in public services and regional development. However, the effectiveness of its implementation is still influenced by limited human resources, fiscal dependence, and weak oversight. Therefore, it is necessary to strengthen institutions, increase fiscal capacity, and maintain sustainable synergy between the central and regional governments so that the goals of regional autonomy can be achieved optimally.